Upaya Peningkatan Kemampuan Literasi melalui Buku Cerita Bergambar Berbasis Kearifan Lokal untuk Siswa Kelas II SD - Himawati, Luh Putu; Sudiana, I Nyoman; Putrayasa, Ida Bagus (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This research aims to determine the characteristics, validity, practicality, and effectiveness of illustrated children's story books based on local wisdom to improve the basic literacy skills of reading and writing in class II elementary school students.Method – This type of research is development (Research and Development). The data collected is in the form of validity, practicality, and effectiveness data. The research instruments used include questionnaires and tests. Validation sheets are used to collect data about the validity of the book. Response questionnaires are used to collect data about teacher responses to measure the practicality of books, Question Instruments are used to collect data about students' reading and writing skills to measure the effectiveness of books. Data was analyzed quantitatively descriptively.Findings – The results of this research show that the product developed is categorized as very valid both in terms of content, graphics, presentation, and language, this is proven by a CV value of 1. The product in the form of the story book "Ready Selem" is categorized as practical. In general, the practicality value of the interest aspect received a score of 24.8 which was categorized as very good, the material presentation aspect received a score of 24.4 which was categorized as very good, and the language aspect received a score of 24.5 which was categorized as very good. In general, the average practicality score is 24.5 in the very practical category. Research Implications – The story book product "Ready Selem" is categorized as effective. This can be seen from the increase in the score obtained before being given the picture story book media compared to after being given the picture story book to class II students at SD Negeri 1 Jatiluwih, with a significant value.